Integrating Population Education within Multilevel Governance in Indonesia: A Systematic Literature Review - Solekhah Maulida; Vishnu Juwono (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2025)
This study investigates the integration of population education within the framework of multilevel governance in Indonesia, focusing on its implementation across formal, non-formal, and informal educational pathways. The objective is to identify the challenges and opportunities that emerge in aligning national policy with decentralized governance practices. Using a systematic literature review method, the study analyzes empirical and theoretical works on education policy, governance models, and demographic strategies, complemented by national data on population education initiatives. The findings reveal a strong concentration of population education in formal institutions, indicating vertical dominance in governance. Meanwhile, non-formal and informal channels remain underutilized, despite their potential for community engagement and contextual adaptability. The study highlights key governance challenges, including fragmented coordination, limited cross-sector collaboration, and weak institutional linkages between government levels. However, it also identifies promising opportunities in decentralized networks and digital policy tools to support more inclusive and adaptive education delivery. The study concludes that a shift toward collaborative, multilevel governance is essential to transform population education into a participatory and equitable policy instrument across Indonesia’s diverse regional contexts.